Determination of shelf life during cold storage of fish fingers coated addition of goji berry - İnanlı, Ayşe Gürel; Amin, Brzo Latif Muhammed (My University, 2022)
The present study was aimed to evaluate shelf life of Pike Barbell (Luciobarbus esocinus Heckel, 1843) experimental samples of fish finger, that ordinarily packed and stored at 4±1°C. Together with the control group, three experimental groups fish finger were obtained with the addition of the goji berry extract into this content by 1% and 2%. According to the findings obtained in this study, it was concluded that fish fingers with goji berry addition had a positive effect on chemical, microbiological and sensory qualities and this study could also establish a basis for many scientific studies with the application of herbal extracts used in experimental samples on various fish products in more different concentration.
Keywords: Luciobarbus esocinus; Shelf life; Cold storage; Goji berry